Characterization and Field Evaluation of Potential Fluorescent Pseudomonas Isolates on Growth and Yield Attributing Characters in Chickpea - Parashuram, R.; Kotasthane, Anil S.; Agrawal, Toshy (International Journal of Bio-resource and Stress Management, 2024)
The present investigation was conducted at the research and instructional farm, College of Agriculture, Indira Gandhi Krishi Vishwavidyalaya, Raipur, Chhattisgarh, India during rabi (October–December 2019) to evaluate the influence of fluorescent Pseudomonas isolates on chickpeas through characterization and field evaluation. Eighty-eight rhizosphere soil samples were derived from different locations in Bastar and Bilaspur districts of Chhattisgarh, India. Potential isolates were required for fundamental research and practical application of plant growth-promoting rhizobacterial strains on different crops. Among eighty-eight isolates, ten fluorescent Pseudomonas (visible under UV light at 360 nm) emitting strong fluorescence were selected for the course of the investigation and characterized for the production of siderophores, phosphate solubilization, indole acetic acid, 1-aminocyclopropane-1-carboxylic acid deaminase, and analysis of antagonistic potential. Of the 10 Pseudomonas isolates, 9704 was identified as the highest phosphate solubilizer, BSP-23 was identified as the highest indole acetic acid producer, and BSP-19 was the highest siderophore producer. Fluorescent Pseudomonas isolates BS-1, BS-4, 9809, BSP-14, and BSP-19 were identified to possess 1-aminocyclopropane-1-carboxylic acid deaminase-producing ability following qualitative analysis. Our present investigation indicates that beneficial effects of fluorescent Pseudomonas could be achieved through simple and cost-effective seed treatment. Three fluorescent Pseudomonas strains, 9704, BS-14, and 9829, consistently increased seed germination and improved plant growth and yield (BS-37.9% and 9704-35.7%) attributes in chickpeas. Besides, confrontation assays performed against R. bataticola expressed varying levels of inhibition. The phylogenetic affinities of 16S rRNA gene sequencing resolved the species identities of selected isolates.